Das Herz Hamburgs? Der Rathausmarkt im Widerstreit von lokaler Politik und medialer Öffentlichkeit in den 1970er und 1980er Jahren. - Strupp, Christoph (Deutsches Institut für Urbanistik, 2019)
Hamburg's town hall square as a central open square in front of the town hall is rhetorically characterized as the "heart of the city", but whether it has actually been a reference point of identity for the citizens since its construction in the late 1840s is an open question. Against this background, the article focuses on the public debate between 1977 and 1982 about its redesign. While it was initially welcomed in the mid-1970s under the impression of changes in urban planning models, the concrete measures and the costs of the rebuilding were soon scandalized by the political opposition and parts of the local media. When the conversion was completed in 1982, the redesigned square met with broad approval among the residents. Although the traffic function, which had been dominant since the inter-war period, was reduced, the square is still considered uncomfortable and attracts larger crowds only for commercial events.
Keywords: Stadtplatz; Rathausplatz; Historischer Platz; Umgestaltung; Platzgestaltung; Platzfunktion; Aufenthaltsqualität; Öffentlicher Raum